2010
DOI: 10.4209/aaqr.2010.03.0017
|View full text |Cite
|
Sign up to set email alerts
|

The Emission and Distribution of PCDD/Fs in Municipal Solid Waste Incinerators and Coal-fired Power Plant

Abstract: The emission and distribution of polychlorinated debenzo-p-dioxins/dibenzofurans (PCDD/Fs) was investigated in two municipal solid waste incinerators (MSWIs) and one coal-fired power plant (PP) in southern Taiwan. Samples were collected from stack flue gases (SFG), bottom residues (BR), super heater (SH), economizer (EC), semi-dry absorber (SDA), bag filter (BF), and fly ash pit (FAP) in MSWIs. Stack flue gases, bottom residues and electrostatic dust collectors (ESD) in PP were also collected. In order to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…The results indicated the concentrations of PBDEs emitted from the stack flue gas of MSWI-A, MSWI-B and TPP were 9.32 ng/Nm 3 , 7.62 ng/Nm 3 , and 5.43 ng/Nm 3 , respectively. The results are comparable with our previous research which is focuses on the distribution of PCDD/Fs in MSWI-A, MSWI-B and TPP (Lin et al, 2010). The PBDE levels of MSWI-A were 116 to 132 times higher than that of the PCDD/F TEQs emitted from MWSI-A during the same period.…”
Section: Pbde and Pbdd/f Concentrations In The Stack Flue Gasessupporting
confidence: 81%
See 1 more Smart Citation
“…The results indicated the concentrations of PBDEs emitted from the stack flue gas of MSWI-A, MSWI-B and TPP were 9.32 ng/Nm 3 , 7.62 ng/Nm 3 , and 5.43 ng/Nm 3 , respectively. The results are comparable with our previous research which is focuses on the distribution of PCDD/Fs in MSWI-A, MSWI-B and TPP (Lin et al, 2010). The PBDE levels of MSWI-A were 116 to 132 times higher than that of the PCDD/F TEQs emitted from MWSI-A during the same period.…”
Section: Pbde and Pbdd/f Concentrations In The Stack Flue Gasessupporting
confidence: 81%
“…Also, long term atmospheric PCDD/F monitoring has been done . The main PCDD/F sources in MSWIs were found to be from fly ashes ; furthermore, the highest content of PCDD/Fs in the MSWIs studied were found to be the ashes in bag filters (Lin et al, 2010). In Taiwan, 72.2% of the electricity comes from thermal power plants, and 67% of those use coal as fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The PCDD/F emissions from coal-fired power plants depend on the type of coal used as well as the APCDs in operation. As seen in Table 7, Mokhtar et al (2014) and 0.147 µg I-TEQ tonne-coal -1 in Lin et al (2010)). Mokhtar et al (2014) indicated that bituminous coal with high sulfur content resulted in slightly lower PCDD/F emissions compared to sub-bituminous coal.…”
Section: Pcdd/f Emissions From Power/heat Generationmentioning
confidence: 99%
“…Consequently, there is a need to limit the emission of such particles. On the other hand, it is well known that industries, such as iron and steel smelters, coal-fired power plants and solid waste incinerators, release a significant quantity of particles to the atmosphere (Dusseldorp et al, 1995;Lin et al, 2010;Ning and Sioutas, 2010). Of these releases, over half the particles go to on-site land disposal, and one quarter are fugitive or point source air emissions.…”
Section: Introductionmentioning
confidence: 99%